2020
DOI: 10.1371/journal.pone.0231015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between degree of hallux valgus and kinematics in classical ballet: A pilot study

Abstract: Hallux valgus is a serious medical concern for classical ballet dancers. Although it is wellknown that progression of hallux valgus is related to inappropriate movement techniques in classical ballet, the kinematic relationship between the degree of hallux valgus and ballet techniques has not been substantiated. To develop proper training methods that prevent progression of hallux valgus, this study aimed to investigate the relationship between the degree of hallux valgus and movement techniques in classical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…[26][27][28] A study of the effect of HV on pelvic stability revealed a significant correlation between increased HV angle and lumbar hyperlordosis. 13 Seki et al 14 found that the more severe the HV, the higher the pelvic 15 As a follow-up to a previous study that examined the effect of HV on lumbopelvic stability and the correlation between HV and the incidence of low back pain, this study objectively verified changes in the 3D kinematics of the pelvic segment through the use of a foot-toe orthosis during gait. In this study, most of the kinematic variables were not affected by the use of foot-toe orthoses, except for some pelvic motions in the frontal and transverse planes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[26][27][28] A study of the effect of HV on pelvic stability revealed a significant correlation between increased HV angle and lumbar hyperlordosis. 13 Seki et al 14 found that the more severe the HV, the higher the pelvic 15 As a follow-up to a previous study that examined the effect of HV on lumbopelvic stability and the correlation between HV and the incidence of low back pain, this study objectively verified changes in the 3D kinematics of the pelvic segment through the use of a foot-toe orthosis during gait. In this study, most of the kinematic variables were not affected by the use of foot-toe orthoses, except for some pelvic motions in the frontal and transverse planes.…”
Section: Discussionmentioning
confidence: 76%
“…26-28 A study of the effect of HV on pelvic stability revealed a significant correlation between increased HV angle and lumbar hyperlordosis. 13 Seki et al 14 found that the more severe the HV, the higher the pelvic obliquity angle during dynamic basic ballet techniques in 17 female classical ballet dancers. In health-related quality of life questionnaires, 469 (48.2%) of 974 patients with HV older than 50 years reported experiencing low back pain, which was significantly different from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on an estimated effect size derived from Seki et al [13], who examined the relationship between the degree of the HV deformity and the kinematics. A sample size of 17 was determined to be sufficient to identify a significant correlation.…”
Section: Subjectsmentioning
confidence: 99%
“…Seki et al (12) conducted investigations to develop appropriate training methods to prevent the progression of HV. A study with female classical ballet dancers at the advanced college-level concluded that the degree of HV is correlated with basic techniques of classical ballet such as the first position.…”
Section: Balletmentioning
confidence: 99%